(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Pancreatic cancer is a tumor lesion originating from the pancreatic ducts or pancreatic parenchyma. Symptoms of pancreatic cancer include nausea, loss of appetite, upper abdominal pain, impaired bowel function, decreased body weight, jaundiced coloration of the sclerae and visible mucous membranes.